The Influence Of Hedonism Lifestyle, Consumptive Behavior And Financial Literacy On Personal Financial Management Of FEB UII Students - Zahra A’yun Syidana; Kartini, Kartini (Cita konsultindo, 2024)
Personal financial management is part of personal financial management which aims to manage one's finances so that they are in accordance with what is planned. Financial management is one of the important things a person needs in maintaining the prosperity of their life in the future. Personal financial management is influenced by a hedonistic lifestyle, consumer behavior and financial literacy. A hedonistic lifestyle, which focuses on seeking unlimited pleasure, is a common problem in modern society, especially among students. With a hedonistic lifestyle, a person will find it difficult to manage their finances because they will always look for pleasure and satisfaction in their life. Consumptive behavior can result in someone prioritizing desires over needs and not knowing the benefits of the products they consume. Someone who has high consumer behavior tends to have poor personal financial management. This is also influenced by financial literacy which aims to achieve financial prosperity and support economic functions. The higher an individual's financial literacy, the better and more efficient his personal financial management will be because an individual will manage his finances as effectively as possible. This research aims to determine the influence of a hedonistic lifestyle, consumer behavior and financial literacy on the personal financial management of FBE UII students. The sampling technique used was probability sampling with the criteria of 150 active FBE UII students. This research is quantitative research and uses primary data obtained directly from respondents via questionnaires and processed using multiple linear regression analysis methods. The results of this research show that there is a significant negative influence on the variables of hedonistic lifestyle and consumer behavior on personal financial management and there is a significant positive influence on the financial literacy variable on personal financial management.